The effects of inulin supplementation on eating behaviours in children and adolescents with obesity: a randomized double-blinded placebo-controlled study - Ekkarit Panichsillaphakit; Chonnikant Visuthranukul; Yuda Chongpison; Natthaya Chuaypen; Tanisa Kwanbunbumpen; Jaraspong Uaariyapanichkul; Sirinuch Chomtho (Nutrition & Metabolism)
Abstract Background Inulin supplementation may restore gut microbiota dysbiosis and modulate appetite control in childhood obesity. This study evaluated the effects of inulin on eating behaviours and explored their relationships with dietary intake, clinical parameters, and gut microbiota in children with obesity. Methods Children aged 7–15 years with obesity were randomly assigned to one of three groups: inulin extracted from Thai Jerusalem artichoke (intervention), maltodextrin (placebo), or dietary fiber advice. All participants received monthly follow-ups with standard dietary and lifestyle guidance for six months. Eating behaviours were assessed at month 0, 3, and 6 using Children’s Eating Behaviour Questionnaires (CEBQs), and their associations with dietary intake, clinical parameters, and gut microbiota were analysed. Results A total of 156 children (mean age: 10.4 ± 2.2 years, mean BMI z-score: 3.2 ± 1.0, 58.3% male) completed the study. Emotional undereating (EUE) significantly decreased in the inulin group compared to the placebo group (p = 0.01). All groups showed reduced food approach subscales, except emotional overeating (EOE), with no significant differences between groups. Among the food approach subscales, food responsiveness was positively correlated with total calorie and fat intakes at baseline and month 3. EOE showed negative correlation with dietary fiber intake/1,000 kcal at month 6. For the food avoidant subscales, satiety responsiveness negatively related to body weight at baseline and proportion of carbohydrate intake (pCHO) at month 6. Slowness in eating was negatively correlated with BMI z-score and pCHO at the end of the study. A 1-point increase in the desire to drink Likert score was associated with a 62.5 mg/day increase in cholesterol intake post-intervention (95%CI: 16.6-108.4). Glucagon like peptide-1 (GLP-1) was inversely correlated with EOE after the intervention. For every 50 ng/L increase in GLP-1, EOE increased by 0.007 points pre-intervention and decreased by 0.037 points post-intervention. CEBQs showed significant associations with Agathobacter at baseline, and with Oscillibacter, UBA1819, and Lachnospiraceae_NK4A136 at month 3. Conclusions Inulin supplementation influenced eating behaviours, particularly reducing EUE. Significant associations between subjective eating behaviours, dietary intake, biochemical markers, and gut microbiota were observed. These findings suggest that inulin supplementation may be a potential strategy for managing childhood obesity through appetite modulation and improving eating behaviours. Trial registration Retrospectively registered at ClinicalTrials.gov (NCT03968003). Registered 30 May 2019.